Verification Concept of Assesment for Physics Education Student Learning Outcome - Yuniarti Suhendi, Herni; Ali Ramdhani, Muhammad; S. Irwansyah, Ferli (International Journal of Engineering and Technology, 2018)
Physics learning is one of the principal pillars in learning science and a foundation of technology development, so that required effective physics learning strategies that is with a good assessment technique. The purpose of this article is to discuss about verification of assessment on learning physics. The methodology for this study is a qualitative analysis with study main source obtained from literature review, then clarified through focus group discussion in lecturers scope. The verification concept reviews the effectiveness of learning outcome asessment system based on the indicators of the improvement of student’s cognitive, affective, and psychomotor domain.  This study showed that the verification of assessment tehnique in learning physics can be done in several approaches, including analytical verification and operational verification. This study recommended that learning physics can work effectively are necessary to apply the design of verified technique assessment so the measurement tool of student’s domain can be accounted objectively and academically.  This study contributed in providing academic paradigm and operational reviews to see the objectivity of assessment in learning physics.